2018
DOI: 10.1155/2018/6237239
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection and Gastric Dysbiosis: Can Probiotics Administration Be Useful to Treat This Condition?

Abstract: Helicobacter pylori (Hp) is responsible for one of the most common infections in the world. The prevalence exceeds 50% of the population in developing countries, and approximately one-third of the adults are colonized in North Europe and North America. It is considered a major pathogenic agent of chronic gastritis, peptic ulcer, atrophic gastritis, gastric cancer, and mucosa-associated lymphoid tissue lymphoma (MALT). Hp colonization modifies the composition of gastric microbiota that could drive the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…effects of Hp-induced DCs in the DC/CD4 + T-cell co-cultures by downregulation of IL-10 production, induction of IL-12p70 and IFN-γ levels, and decreased Treg generation. These observations may confirm the results of previous studies on the role of microbiota composition in resistance against Hp infection 43. The fact that only the Hp-antagonistic LAB strain (Lr) exerted this effect points out the need for testing more LAB strains as a potentially useful concomitant component of the standard eradication therapy.…”
supporting
confidence: 87%
“…effects of Hp-induced DCs in the DC/CD4 + T-cell co-cultures by downregulation of IL-10 production, induction of IL-12p70 and IFN-γ levels, and decreased Treg generation. These observations may confirm the results of previous studies on the role of microbiota composition in resistance against Hp infection 43. The fact that only the Hp-antagonistic LAB strain (Lr) exerted this effect points out the need for testing more LAB strains as a potentially useful concomitant component of the standard eradication therapy.…”
supporting
confidence: 87%
“…The gastric colonization pattern is mainly based on Bacteroidetes and Firmicutes. Streptococcus strains predominate in the gastric microbiota, beside Prevotella and Veillonella [63]. It has been shown that PPIs chronic administration was associated to several adverse events as increased bacterial concentration and translocation and gastric stasis [64].…”
Section: The Influence Of Ppis On the Gut Microbiotamentioning
confidence: 99%
“…It has been proposed that Hp initially increases acid secretion and acid reflux, and decreases lower esophageal sphincter (LES) pressure, thereby increasing the risk of GERD and its related BE and EAC, whereas the subsequent Hp ‐induced atrophic gastritis might normalize this risk . However, hypochlorhydria, as a consequence of Hp ‐related atrophic gastritis, seems to induce alterations of the gastric microbiota (GM), namely gastric dysbiosis, which, beyond gastric pathologies, including gastric cancer, might also contribute to the BE−EAC sequence . In this regard, Campylobacter is among the most influential genera in Hp‐ induced atrophic gastritis specimens and gastric atrophy−related GM may be a significant contributor to gastric oncogenesis .…”
Section: Newer Considerationsmentioning
confidence: 99%
“…It seems, therefore, that Campylobacter species related to Hp‐ induced atrophic gastritis could be etiological agents of the chronic esophageal inflammation that results in EAC development . Moreover, the GM transformation from predominantly Gram‐positive to mostly Gram‐negative bacteria (including Hp ) suggests that dysbiosis is involved in the pathogenesis of the GERD−BE−EAC sequence …”
Section: Newer Considerationsmentioning
confidence: 99%